Traffic Management in Telecommunication Networks Using Artificial Intelligence (Texas Journal of Engineering and Technology, 2022)
Traffic analysis and management tasks form the basis of modern telecommunication management processes. The goal of such solutions is to provide a balance between the volume of traffic, service and telecommunication resources. These tasks, as well as ensuring the effectiveness of technical solutions for a sufficiently long time, are carried out at the stage of designing telecommunications. In this article, a scientific research was conducted on the management of traffic in telecommunication networks using artificial intelligence methods.